High Risk Persistent Air Leaks in Giant and Diffuse Bullae Lung Disease Salvaged by Urgent Endobronchial Valve (EBV) Insertion - Wan, Jen Lye; Abdul Rahaman, Jamalul Azizi; Adrian Ooi Seng Wae; Mohd Said , Nor Hayati (The Interventionalist Journal, 2022)
Persistent air leak (PAL) is a common complication of pneumothorax despite intercostal drainage. Neither pneumothorax management guidelines from the American College of Chest Physicians (2001) and the British Thoracic Society (2010) recommended bronchoscopy, much less endobronchial valves as management for PAL. We describe a case of a 62-year-old gentleman, an active smoker of 40 pack years, who had history of left-sided pneumothorax in 2019 that was treated conservatively. In August 2021, he presented with shortness of breath and right-sided chest discomfort. His Chest X-ray revealed a right tension pneumothorax. A chest drain was inserted with much clinical improvement. However, he had persistent air leak despite 30 days on a chest drain. In view of his refusal for surgical intervention, the patient underwent endobronchial valve insertion as a salvage procedure into his right upper lobe. His PAL resolved within 24 hours, and he was discharged the next day.